Syndromic Surveillance of Sexually Transmitted Infections in Private General Practices in the Gauteng Province - Soni, Samad Abdul (My University, 2006)
The epidemic of Sexually Transmitted Infections (STIs), including HIV infection, is one of the major challenges facing South Africa at the present time. Controlling the epidemic of conventional STIs will decrease the suffering and complications caused by these diseases as well as the spread of HIV/AIDS. In order to manage patients in an efficient and cost-effective way, the WHO has advocated syndromic management. This approach is characterised by the management of persons with STIs by providing treatment for a group of diseases, which may cause one or more signs or symptoms, rather than by treating a specific disease. The incidence of STIs is very high in South Africa and many patients with STIs are consulting private general practitioners but very little information is available on syndromic management in general practice. To this view, sexually transmitted diseases tally sheets were given to twenty self selected private general practitioners and were requested to complete sheets for all STI and non- STI patients for a period of eight weeks. Also a demographics questionnaire with regard to the doctors and their practices was given to the doctors for completion. The data was captured and analysed using the Microsoft Access and the EpiInfo 6 statistical package 5 The results indicated that although private general practitioners manage a fair number of STI patients, not all are familiar with syndromic management. While recognising that the respondents were self-selected, 19 (95%) of the 20 participating doctors were very keen to attend courses on syndromic management. It is recommended that more information be made available to general practitioners on syndromic management.
Faculty of Health Sciences School of Family Medicine 0335022 asmartc@yahoo.co.uk
Keywords: Syndromil; Surveillance; Sexually Transmitted; Infections; Private general Practitioners